Pengaruh Citra Produk, Pengalaman Produk, dan Brand Tribalism Terhadap Loyalitas Produk Pada Produk Thrift Fashion Di Yogyakarta - Zalzalah, Guruh Ghifar; Arum Sari, Pinesti Ragil; Farhan, Fikri (Akmenika: Jurnal Akuntansi dan Manajemen, 2024)
This research aims to determine the influence of product image, product experience, and brand tribalism on product loyalty in Thrift Fashion products in Yogyakarta. The study was conducted in the Special Region of Yogyakarta in 2023, with a sample size of 130 respondents. The technique used in this research employed non-probability sampling using purposive sampling method. Data analysis in this research used IBM SPSS Statistics 26 with multiple linear regression analysis technique at a significance level of α = 0.05. The results of the research indicate that partially, product image, product experience, and brand tribalism have a positive and significant effect on product loyalty. Simultaneously, product image, product experience, and brand tribalism have a significant effect on product loyalty. The magnitude of the influence of product image, product experience, and brand tribalism on product loyalty is indicated by the Adjusted R Square value of 56%.